The Effect of Teacher–Child Race/Ethnicity Matching and Classroom Diversity on Children's Socioemotional and Academic Skills. Issue 3 (23rd June 2019) - Rasheed, Damira S.; Brown, Joshua L.; Doyle, Sebrina L.; Jennings, Patricia A.
Abstract : Mounting evidence suggests teacher–child race/ethnicity matching and classroom diversity benefit Black and Latinx children's academic and socioemotional development. However, less is known about whether the effects of teacher–child matching differ across levels of classroom diversity. This study examined effects of matching on teacher‐reported child outcomes in a racially/ethnically diverse sample of teachers and children, and classroom diversity moderation using multilevel models. Data were drawn from a professional learning study involving 224 teachers ( M age = 41.5) and 5, 200 children ( M age = 7.7) in 36 New York City elementary schools. Teacher–child race/ethnicity matching was associated with higher child engagement in learning, motivation, social skills, and fewer absences. Classroom diversity moderated matching such that teacher–child mismatch was related to lower engagement, motivation, social skills, math and reading scores in low‐diversity classrooms, but not in high‐diversity classrooms. Implications for practice and policy are discussed.